2012
DOI: 10.1200/jco.2011.39.2100
|View full text |Cite
|
Sign up to set email alerts
|

Increased Body Mass Index Is Associated With Improved Survival in United States Veterans With Diffuse Large B-Cell Lymphoma

Abstract: A B S T R A C T PurposeObesity increases the risk of death from many malignancies, including non-Hodgkin's lymphoma (NHL). In diffuse large B-cell lymphoma (DLBCL), the most common form of NHL, the association between body mass index (BMI) at diagnosis and survival is unclear. Patients and MethodsWe evaluated the association between BMI at diagnosis and overall survival in a retrospective cohort of 2,534 United States veterans diagnosed with DLBCL between October 1, 1998 and December 31, 2008. Cox modeling was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
78
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 37 publications
(7 reference statements)
9
78
3
1
Order By: Relevance
“…In the present study, we showed that an extremely low BMI (<18.5 kg/m 2 ) had a negative prognostic impact, with results similar to those reported by Park et al [12]. However, contrary to the results reported by Carson et al [11] showing a linear, proportional relationship between BMI and estimated survival rate, we observed a non-linear trend between BMI and the estimated 3-year survival. Furthermore, in contrast to the previous report [11], we demonstrated that a very high BMI (≥30.0 kg/m 2 ) had an unfavorable prognosis, which is in agreement with the findings of a recent multiethnic cohort study [32].…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…In the present study, we showed that an extremely low BMI (<18.5 kg/m 2 ) had a negative prognostic impact, with results similar to those reported by Park et al [12]. However, contrary to the results reported by Carson et al [11] showing a linear, proportional relationship between BMI and estimated survival rate, we observed a non-linear trend between BMI and the estimated 3-year survival. Furthermore, in contrast to the previous report [11], we demonstrated that a very high BMI (≥30.0 kg/m 2 ) had an unfavorable prognosis, which is in agreement with the findings of a recent multiethnic cohort study [32].…”
Section: Discussioncontrasting
confidence: 76%
“…Therefore, initial presentation with an extremely low or high BMI at diagnosis may be considered as a negative prognostic factor in Asian DLBCL patients. Several studies demonstrated that a higher BMI is associated with a higher prevalence [30,31] and with favorable outcomes in DLBCL patients [11], while another study found no prognostic effect [14] (Table 7). In the present study, we showed that an extremely low BMI (<18.5 kg/m 2 ) had a negative prognostic impact, with results similar to those reported by Park et al [12].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients with higher body weight and higher body mass index have been shown to profit from prolonged rituximab treatment. 14,23 Men in the NHL13 had a significantly higher body mass index (median 26 versus 25.4,…”
Section: Discussionmentioning
confidence: 99%
“…In acute promyelocytic leukemia, for example, elevated BMI before diagnosis is associated with increased disease incidence, and elevated BMI is associated with an increased risk of relapse after treatment [6 -8]. Elevated BMI is also associated with an increased incidence of diffuse large B-cell lymphoma [9], but patients who are overweight or obese at the time of diagnosis demonstrate improved survival compared with those with a healthy-weight BMI [10].…”
Section: Introductionmentioning
confidence: 99%